2004
DOI: 10.1007/s00066-004-1200-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Various Parameters in Detecting Chromosomal Aberrations by FISH to Describe Radiosensitivity

Abstract: To detect a difference in chromosomal aberrations between healthy and radiosensitive individuals, the parameters "frequency of breaks per metaphase", "complex chromosomal rearrangements", and "translocations" are most suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
(71 reference statements)
0
41
0
Order By: Relevance
“…This study found more fibrosis in patients with higher levels of in vitro induced lethal aberrations. In addition, using three color whole chromosome FISH, Keller et al found higher levels of breaks, complex chromosomal rearrangements and translocations, in in vitro irradiated lymphocytes from patients who had developed grade 3 or greater late radiation toxicity including fibrosis (118). This study; however, was based on only 5 sensitive and 11 normally responding patients.…”
Section: Predictive Biomarkers For Radiation Fibrosismentioning
confidence: 83%
“…This study found more fibrosis in patients with higher levels of in vitro induced lethal aberrations. In addition, using three color whole chromosome FISH, Keller et al found higher levels of breaks, complex chromosomal rearrangements and translocations, in in vitro irradiated lymphocytes from patients who had developed grade 3 or greater late radiation toxicity including fibrosis (118). This study; however, was based on only 5 sensitive and 11 normally responding patients.…”
Section: Predictive Biomarkers For Radiation Fibrosismentioning
confidence: 83%
“…Quite a number of techniques are intended to be used in the detection of individual radiosensitivities, such as chromosomal aberrations [8,11], 24-color FISH [14,15], micronuclei [32], DNA-PKCS and Ku (p70/p80) [3], to name just some of the approaches. As our major interest with regard to the application of the comet assay is also directed at the monitoring of individual radiosensitivities, in particular, of tumor patients who received a radiotherapy, our test was optimized to have maximum sensitivity in the dose range between 0-2 Gy and to allow the measurement of DNA repair after a single dose of 2 Gy (corresponding to the dose per fraction in conventional radiotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations were calculated and given as Spearman's coefficient of rank correlation (rs; SPSS for Windows, Version 11.5, Munich, Germany) [12,21].…”
Section: Methodsmentioning
confidence: 99%